MANAJEMEN PERUBAHAN DAN INOVASI DALAM ORGANISASI - Nursahwal (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
This article aims to explore the concepts, approaches, models, driving factors, and benefits of change and innovation management within organizations to address the increasingly complex and competitive organizational environment. This study employs a literature review method by collecting data from primary sources such as books and journal articles. The data collection technique involves searching and analyzing various relevant literature, while the analysis technique used is descriptive analysis, which includes stages such as topic identification, literature collection and classification, systematic data presentation, contextual understanding, and conclusion drawing. Change management focuses on a systematic process of implementing strategies to encourage individual and organizational adaptation to new conditions, ensuring that changes are accepted, implemented, and sustained. In contrast, innovation management is a strategic process of creating, managing, and implementing new ideas to provide added value to the organization and establish a competitive advantage. Innovation encompasses product, process, and market aspects, enabling organizations to quickly respond to external changes and meet customer needs. This literature review is expected to provide valuable insights for academics and practitioners in developing adaptive, innovative, and sustainable organizations. Additionally, the study's findings can serve as practical recommendations for organizational leaders, managers, and business practitioners in designing and managing change and innovation strategies effectively within organizations.